American Transcendentalism and the Idea of Nature: Philosophical Dimensions in the Ukrainian Context - Руденко, С.; Труш, Т. (Київський національний університет імені Тараса Шевченка, 2025)
Relevance of the research. Considering that over recent years, there has been an increasing interest in American transcendentalism within Ukrainian intellectual discourse, highlighting the need to analyze one of its central concepts: the notion of nature, which for transcendentalists acquires the significance of an ethical indicator, an ontological category, an anthropological essence, and a socio-political component. American Transcendentalism, as a philosophical and literary movement of the 19th century, played an important role in the formation of the modern philosophical understanding of nature, its relationships with man and society. Today, when the United States of America has a significant influence on the life of the world, especially on politics, economics, culture, philosophy, etc., such influence requires researchers to turn to the origins of national consciousness to establish the essential features of worldview guidelines. In other words, turning to the history of American philosophy contributes to a better intercultural dialogue of modernity. The purpose of this study is to analyze the concept of nature within American transcendentalism in the works of R. W. Emerson, H. D. Thoreau, and W. Whitman as well as understand its meaning in the Ukrainian intellectual context. Conclusions. The concept of nature in the work of American transcendentalists had a broader meaning than the external world, not transformed by man. Nature was understood as the essence and driving force of the world, where person, culture, and society are subject to its laws. Therefore, the key to improving human life was to harmonize the interaction of man and nature. The issues of forming a national identity, finding one's scientific path, the relationship between the individual and authorities, man and nature in the first century of US independence can also be useful for the Ukrainian experience. The works of thinkers have recently been translated into Ukrainian, and their interpretation is also changing both in the Ukrainian history of philosophy and in literary studies. The need to revise the interpretations of their work in contrast to Soviet interpretations is an urgent issue that stimulates scientific interest in American transcendentalism.

Актуальність. З огляду на те, що останніми роками в українському інтелектуальному просторі спостерігається особливий інтерес до американського трансценденталізму, існує потреба і в розгляді центрального для трансценденталізму поняття природи, яке для трансценденталістів набуває значення етичного індикатора, онтологічної категорії, антропологічної сутності та соціально-політичного компонента. Американський трансценденталізм як філософсько-літературний рух XIX ст. відіграв важливу роль у формуванні сучасного філософського розуміння природи, її взаємозв’язків із людиною та суспільством. На сьогодні, коли Сполучені Штати Америки мають вагомий вплив на життя світу, особливо на політику, економіку, культуру, філософію тощо, подібний вплив вимагає від дослідників звертатися до витоків національної свідомості з метою встановлення сутнісних рис світоглядних орієнтирів. Інакше кажучи, звернення до історії американської філософії сприяє кращому міжкультурному діалогу сучасності. Метою статті є аналіз концепції природи в американському трансценденталізмі на прикладі творів Р. В. Емерсона, Г. Д. Торо, В. Вітмена, а також осмислення її значення в українському інтелектуальному контексті. Висновки. Поняття природи у творчості американських трансценденталістів мало ширше значення, ніж зовнішній світ, не перетворений людиною. Природа розумілась як сутність та рушійна сила світу, де і людина, і культура, і суспільство підпорядковані її законам. Тому ключ до покращення людського життя полягав у гармонізації взаємодії людини та природи. Питання формування національного ідентитету, пошуку власного наукового шляху, взаємин індивіда і влади, людини та природи у першому столітті незалежності США можуть бути корисними і для українського досвіду. Твори мислителів нещодавно було перекладено українською мовою, також змінюється й їхнє трактування як в українській історії філософії, так і в літературознавстві. Необхідність перегляду інтерпретацій їхньої творчості на противагу радянським тлумаченням є нагальним питанням, що стимулює науковий інтерес до американського трансценденталізму.
Американський трансценденталізм і ідея природи: філософські виміри в українському контексті